Minimization of torque ripples in direct torque control of induction motor at low speeds - Abdullah Ajlan, Abdullah Ali (2016)
Direct Torque Control (DTC) of induction motor has attracted a considerable attention in the motor drives industry. The key merits of DTC include fast torque dynamic response, simple structure, insensitivity to motor’s parameters. Nevertheless, DTC inherently suffers from two major downsides namely: high torque ripples and variable switching frequency. This thesis presents a new technique to minimize the torque ripples inherited in the digital-based DTC of induction motor. The typical discrete-based DTC imposes a delay time which frequently allows the torque to overshoot beyond hysteresis bands. This triggers the selection of reverse voltage vectors which, in turn, cause large torque decrements. The torque ripples become of great significance at low speeds where torque overshoot is most likely to occur due to steep positive torque slope. A multi-level DC link voltage is proposed to vary the DC voltage of Voltage Source Inverter (VSI) according to motor’s speed. By varying the DC link voltage, the torque slopes can be controlled and, hence, the torque overshoots are mostly avoided. Therefore, the torque ripples are significantly minimized. The viability of proposed technique has been validated using MATLAB/Simulink software. Results show the proposed technique may yield over 50% reduction in the RMS torque ripples while maintaining a low switching frequency. Also, the torque dynamic response is maintained as good as in the conventional DTC scheme